Sistem Informasi Laporan Berbasis Website (Web-SIrap) Meningkatkan Intensitas Pendampingan Orang Tua - Putu Puji Kanti Laksani; Putu Nanci Riastini (Universitas Pendidikan Ganesha, 2022)
The process of preparing report cards is still conventional, in the preparation of report cards using software in the form of excel. With the excel report card, the teacher gives an assessment only at the end of the semester. Parents find it challenging to monitor their child's development when following the lesson. This study aims to develop a website-based report card information system (Web-SIRap) to increase the intensity of parental assistance. This type of research is development research using the ADDIE model. The research subjects consisted of 2 educational evaluation experts. The subjects of the media trial were the parents of 9 students and 3 teachers. The research method used is observation, questionnaires, and interviews. The instruments used to collect data were observation guidelines, questionnaire/questionnaire sheets, interview guidelines, and rating scale sheets. The technique used in analyzing the data is descriptive quantitative statistical analysis and inferential statistics. The study results, namely the content validity score from the expert, got a result of 1.00, so the content validity was very high. The results of the analysis of user responses are that teachers are 100% (very good) and parents are 84% so (good). Based on the significant (2-tailed) result, the result was 0.000 < 0.05, so the result was a significant increase in the intensity of parental assistance. It was concluded that the website-based report card information system (Web-SIRap) was suitable for learning and could increase the intensity of parental assistance.